2001
DOI: 10.1023/a:1013370529366
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The mole faction of drug (relative to competing ions of like polarity) is the crucial determinant of the extent to which it can carry charge across the skin during iontophoresis. The outward electromigration of Cl-, in the sense opposite to drug delivery, may offer a useful means by which to optimize iontophoretic efficiency in the absence of competing cations in the anode formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Application of an electric current dramatically increased the flux of both molecules even though the computation of transport numbers indicated that >99% of the charge was carried by TrisH+ from the buffer solution and subdermal chloride ions (transport numbers of NTX and BUP at pH 6 were 8.2 × 10 –4 and 4.5 × 10 –4 , respectively). This was expected and consistent with previous findings. , Importantly, the therapeutic target flux for BUP was achieved by iontophoresis.…”
Section: Resultssupporting
confidence: 89%
“…Application of an electric current dramatically increased the flux of both molecules even though the computation of transport numbers indicated that >99% of the charge was carried by TrisH+ from the buffer solution and subdermal chloride ions (transport numbers of NTX and BUP at pH 6 were 8.2 × 10 –4 and 4.5 × 10 –4 , respectively). This was expected and consistent with previous findings. , Importantly, the therapeutic target flux for BUP was achieved by iontophoresis.…”
Section: Resultssupporting
confidence: 89%
“…First, it is predictably altered by the ionic mole fraction, observations which have also been reported in transdermal iontophoresis. 37, 38 Importantly this provides a way to modify or predict changes in the ejection rate of a target ion. Secondly, the calculated transport number systematically underestimated the observed values, as larger quantities of DA were ejected than predicted from migration.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular transport mechanisms in individual pores (e.g., protein ion channels and synthetic channels , ) and in materials containing pores of nanometer dimensions (e.g., zeolite catalysts and skin) are of interest throughout chemistry and biology. It is generally recognized that transport selectivity, based on a chemical or physical property of the permeant, is often observed in pores when the size of the pore is sufficiently small that interactions between the pore surface and permeant influence local transport dynamics.…”
Section: Introductionmentioning
confidence: 99%